Dickens’s Haunted Christmas: The Ethics of the Spectral Text - Brad Fruhauff (University of Edinburgh, 2008)
The question of haunting itself has its own interest, but one might also wonder why Dicken's Christmas Carol - a Christmas story - should be at all haunted. While some connection between Christmas, winter and the supernatural can be traced back through Shakespeare and no doubt beyond, Dickens seems especially interested in the manifestation of ghosts and phantoms at Christmas-time. Indeed, by publishing his own and many others’ seasonal ghost stories in his magazines, Household Words and All the Year Round, he can be attributed with making the ghost story a sort of Victorian Christmas tradition (Cox xiii). Moreover, in his Christmas tales, Dickens saw no contradiction in combining the Gothic effects of ghost stories with sentimental scenes to present his religio-social message of charity, compassion and communal affection.